PELAKSANAAN KEWENANGAN BADAN PERMUSYAWARATAN DESA (BPD) DI MULYA SUBUR - Fitria Manda Sari Susanti; Sofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Abstract: ImplementationAuthorityConsultative Body(BPD) inFertileMulyasubur.The purposeofthis studywas to determinehow theimplementation oftheauthority possessedby theVillage Consultative BodyFertileVillageMulyasubursubdistrictPelalawanMortarBase. This studyreliedon interviewswithkeyinformantsamongresearchersthatresearchershavespecifiedbeforehand.Whothenmake observationstosee theevents thatoccur in the field. The resultsshowedthatthe implementation of theauthoritypossessedby theVillageConsultative BodyinBaseVillageMulyasubursubdistrictfertileDimplesPelalawanwholefieldhas not done well. Thishappensdue tothe lack of qualityhuman resourceswhich includelevelofeducationandlevel of understandingpossessedby theVillage ConsultativeBodyinthevillage.Keywords: Implementation, Authority, AgencyVillage Consultative